Survey on the Effectiveness of the Online Learning Process Due to the Coronavirus Pandemic in Physical Education - Indung Pranata; Ari Wibowo Kurniawan (Physical Education and Sports: Studies and Research, 2022)
Background: Since the outbreak of the coronavirus covid-19 in Indonesia, education has offered online learning. Online learning requires system support, namely hardware (smartphone, tablet, or laptop/personal computer), internet network, and human resources. However, the implementation of online learning encounters several challenges and obstacles, especially online learning in physical education in elementary schools. Objectives: The purpose of this study was to determine and examine the effectiveness of the online learning process due to the coronavirus pandemic in Physical Education and Health subjects at SD Negeri 6 Sumbermanjingkulon, Pagak District, Malang Regency. Methods: This study used a descriptive research design with a survey method. This study involved 48 elementary school students. The data collected through a questionnaire method or a google form-based questionnaire that has been tested for validity by an expert. Data analysis was carried out on five indicators in the study. The indicators consist of student interest, interest, benefits, learning facilities and infrastructure, and quality of interaction. Results: The results of the study indicate that the effectiveness of online learning at SD Negeri 6 Sumbermanjingkulon is in the criteria of being quite effective with a percentage of 46.90%. Conclusion: Based on the results of the study, it shows that overall online learning in physical education and health subjects is quite effective, but the percentage obtained between quite effective and ineffective is only a slight difference.